Mighty movers. Emergency. ([Los Angeles, Calif.] : Paradise Press, 2004)
Pictures and short descriptions of emergency vehicles including fire engines, police vehicles and ambulances.
On board pages.
Cover title.
Keywords: Emergency vehicles -- Juvenile literature; Fire engines -- Juvenile literature; Police vehicles -- Juvenile literature; Ambulances -- Juvenile literature; Board books